ENHANCEMENT IN E-LEARNING & M-LEARNING USING 3D - ABDALRASSUAL JASSIM, Mustafa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
3D technology is getting much popularity in the recent era of technology this is the technology in which we can see the image from different angles. TVs and iPhones are available in 3D, 3D technology is used in different application and it is increasing day by day. Now a days 3D cameras, 3D webcams, 3D movies available. In 3D seeing images come alive. 3D projection has been seemed a technology long on potential but short on practicality. New prototype appeared a trade shows year after year, and while they were drool-worthy, manufacturers just couldn’t pull 3D into the production stage. These days 3D are used in different sectors like, corporate enterprise training, health industries and in teaching learning process. Present study discusses that we can Enhance E-learning and M-Learning with help of 3D.